(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article presents the results of expeditionary studies of the sea buckthorn. We did research methods, techniques of selection, morphological evaluation of selection of economically valuable features of plantations of sea buckthorn of Issyk-Kul Lake. For the first time, we discovered thornless sea buckthorn in wild populations around Lake Issyk-Kul. Vegetative and seed propagation in culture were started experimentally.